(untitled) (Fiep Bulletin - online, 2012)
Physical education is undergoing paradigm shifts where theoretically there is the enrichment of content can work where theeducation of the student. The study aims to analyze the content of classes of physical education professionals from private colleges in thestate of Rio de Janeiro in relation to activities covered. The study population consisted of professionals working in the area of physicaleducation. The sample, chosen at random and drawn from a universe of 09 teachers in overcrowded schools from private schools in thecity of Rio de Janeiro, Meier neighborhood was comprised of 13 professionals, with 04 females and 09 males, who work in elementaryeducation. According to the literature and analyzing the results, we noticed certain complacency on the part of teachers, this perhaps linkedto factors such as lack of recognition by the school itself. In addition, you can include a lack of courage or willingness to dare to dislodgethemselves and their relative certainties as well as the absence of a regular program of continuing education and encouragement by theschool. When the didactic use of this content is done without this reflection, the practice loses its meaning and the classes end up going intothe molds and technical merit by taking to make fazer.Sugere to a later study in which it can add a larger number of professionals andregions to obtain an exact dimension of this table of contents and study what can be done to transform this system to teach the BodyCulture Movement and do not let all the contents of Physical Education be forgotten by professionals in the area.